Son yıllarda Türkiye-İspanya ilişkileri ve medeniyetler ittifakı girişimi - Örmeci, Ozan (Ozan Örmeci, 2025)
Türkiye ile İspanya ilişkileri, son yıllarda, bu konuda fazla yazılıp çizilmemesine karşın, oldukça uyumlu ve müttefiklik ruhuna yakışır şekilde ilerleyen araştırılması gereken bir husustur. Türkiye’deki İslamcı eğilimli hükümetin Avrupa’daki en yakın müttefik ve destekçilerinden olan İspanya, özellikle Filistin Sorunu konusundaki duruşu, İslamofobi’ye karşı mücadelesi ve Türkiye ile birlikte liderliğini yaptığı Medeniyetler İttifakı girişimiyle Türkiye’de takdir toplamaktadır. Bunun yanı sıra, iki ülke arasında son dönemde yoğunlaşan ekonomik ilişkiler ve askeri teknoloji alanındaki iş birliği, iki devleti birbirine yakınlaştıran faktörlerdendir. Bu çalışmada, Türkiye-İspanya ilişkileri farklı boyutlarıyla değerlendirilecek ve Medeniyetler İttifakı girişimi incelenecektir.

Although not much has been written about it in recent years, relations between Türkiye (Turkey) and Spain have been progressing in a harmonious and alliance-like manner, which deserves further investigation. Spain is one of the closest allies and supporters of Türkiye’s Islamist-leaning government in Europe and is especially admired in Türkiye for its stance on the Palestinian Question, its fight against Islamophobia, and the Alliance of Civilizations initiative, which it co-leads with Türkiye. In addition, the recently intensified economic relations between the two countries and cooperation in the field of military technology are among the factors that bring the two states closer to each other. In this study, Türkiye-Spain relations will be evaluated in different dimensions and the Alliance of Civilizations initiative will be examined.
Turkish-Spanish relations in recent years and the alliance of civiliations initiative
Keywords: Türkiye-İspanya ilişkileri; Recep Tayyip Erdoğan; Pedro Sánchez; Medeniyetler İttifakı; José Luis Rodriguez Zapatero; Turkish-Spanish relations; Alliance of Civilizations